2004
DOI: 10.1103/physrevb.70.045104
|View full text |Cite
|
Sign up to set email alerts
|

Charge disproportionation and spin ordering tendencies inNaxCoO2

Abstract: The strength and effect of Coulomb correlations in the (superconducting when hydrated) x ≈1/3 and "enhanced" x ≈2/3 regimes of NaxCoO2 are evaluated using the correlated band theory LDA+U (local density approximation of Hubbard U) method. Our results, neglecting quantum fluctuations, are: (1) allowing only ferromagnetic order, there is a critical Uc = 3 eV, above which charge disproportionation occurs for both x=1/3 and x=2/3, (2) allowing antiferromagnetic order at x=1/3, Uc drops to 1 eV for disproportionati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
143
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(165 citation statements)
references
References 63 publications
18
143
4
Order By: Relevance
“…The electronic structure of these compounds was calculated in the local (spin) density approximation (LSDA). The inclusion of a Hubbard repulsion parameter U in the calculation yields the two magnetically different regimes for x < 0.5 and x > 0.5 [14] that are observed experimentally. The calculation also explains [15] the absence of pockets of the Fermi surface, as was registered in angle-resolved photoemission (ARPES) experiments for x = 0.3 [16], x = 0.6 [17] and x = 0.7 [18].…”
Section: Introductionmentioning
confidence: 93%
“…The electronic structure of these compounds was calculated in the local (spin) density approximation (LSDA). The inclusion of a Hubbard repulsion parameter U in the calculation yields the two magnetically different regimes for x < 0.5 and x > 0.5 [14] that are observed experimentally. The calculation also explains [15] the absence of pockets of the Fermi surface, as was registered in angle-resolved photoemission (ARPES) experiments for x = 0.3 [16], x = 0.6 [17] and x = 0.7 [18].…”
Section: Introductionmentioning
confidence: 93%
“…It is this difference in the band center (i.e. the on-site energy) that drives this transition, as happened in Na x CoO 2 [17] or V 2 O 3 . [18] Keeping the structure (and symmetry) cubic inhibits such an orbital-ordering transition, implying close interplay between structural distortion (even though tiny) and orbital ordering in LDA+U calculations in this system as suggested in CaCrO 3 .…”
Section: Inclusion Of Correlation Effectsmentioning
confidence: 99%
“…The magnetic moments of the d-shells serve as indicators of the redistribution of the d-electron spin and charge density between the Co ions in their triangular lattice. 12,24,25,27,29 In the previous study we have reported about the LS "phase" of the electrons, 29 see Fig. 1(c).…”
Section: B Electronic Statesmentioning
confidence: 99%
“…In subsequent calculations it was established, that when the coupling with such order is taken into account, the LS states with hole disproportionation indeed appear, possessing charge/spin patterns of various types (the zig-zag, striped, honeycomb, and hexagonal) which depend on the presumed Na arrangement. [24][25][26][27][28][29] However the ordering of Na + ions drastically changes the electronic low-energy states, 24 and the KSL structure expected for the phase x = 2/3 was not obtained in the LS-states of the lattice even with the realistic sodium structure. 29 The aim of the present study is to investigate conditions for the origin of a metallic state with the KSLstructure of the d-electron charge and spin disproportionation in cobaltates, employing the ab-initio calculations for the system with ordered Na ions.…”
Section: Introductionmentioning
confidence: 99%